Iron catalytic material as well as preparation method and application thereof

By forming an oxygen-containing iron layer on the iron substrate, the problem of high metal ion leaching rate of cathode materials in electrochemically activated persulfate technology is solved, and the electrode life is extended and the pollutant degradation effect is improved.

CN119386872APending Publication Date: 2025-02-07SHANGHAI UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411610186.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing electrochemically activated persulfate (E-PDS) technology, the metal ion leaching rate of the cathode material is high, resulting in a short electrode life and further improvement in degradation performance.

Method used

By forming an oxygen-containing iron layer, including γ-FeOOH, α-Fe2O3 or Fe3O4, as an iron catalytic material, the leaching of iron ions is reduced and converted into Fe3O4/Fe catalytic material through electrochemical degradation reactions, and extending the Electrode life.

Benefits of technology

It effectively reduces the leaching of iron ions, extends the service life of the electrode, and maintains efficient pollutant degradation effect at lower current density and lower PDS concentration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386872A_ABST
    Figure CN119386872A_ABST
Patent Text Reader

Abstract

The invention provides an iron catalytic material as well as a preparation method and application thereof. The method comprises the following steps: carrying out in-situ etching on an iron substrate by adopting an iron salt solution with the concentration of 20-80 mM so as to form an oxygen-containing iron layer containing gamma-FeOOH on the surface of the iron substrate, thereby obtaining the gamma-FeOOH / Fe iron catalytic material, or after the gamma-FeOOH / Fe iron catalytic material is obtained, the gamma-FeOOH / Fe iron catalytic material is calcined at the temperature of 300-500 DEG C in the inert atmosphere, so that gamma-FeOOH in the gamma-FeOOH / Fe iron catalytic material is converted into alpha-Fe2O3, an oxygen-containing iron layer containing alpha-Fe2O3 is formed on the iron base material, and the alpha-Fe2O3 / Fe iron catalytic material is obtained. The gamma-FeOOH / Fe and the alpha-Fe2O3 / Fe can serve as cathode materials to be used for electrochemically activating persulfate to degrade pollutants, metal active sites are effectively fixed and protected through the oxygen-containing iron layer on the surface, leaching of iron ions on a cathode is reduced, and therefore the service life of the cathode is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental catalysis, and in particular relates to an iron catalytic material and a preparation method and application thereof. Background Art

[0002] The treatment and recycling of pesticide-containing wastewater is a key strategy to improve the level of industrial water conservation and utilization and promote the comprehensive green transformation of the economy and society. In order to accelerate the utilization of sewage resources, promote the solution of water resource shortages, water environmental pollution, and water ecological damage, and promote high-quality development, it is necessary to promote the development of various effective and environmentally friendly methods to solve water pollution problems. With the development of industrialization and the continuous increase of the global population, human society is facing increasingly serious resource depletion and environmental crises.

[0003] Advanced oxidation processes (AOPs), such as Fenton / Fenton-like oxidation, ozone oxidation / catalytic ozone oxidation, photocatalytic oxidation and electrochemical oxidation, all utilize hydroxyl radicals ( ) as reactive oxygen species (ROS) to degrade pesticides, and have a good effect. Among them, the sulfate radical produced by the Fenton-like oxidation based on persulfate (PDS) has a higher redox potential (2.5-3.1V) and a longer half-life (30-40 μs).

[0004] Electrochemically activated PDS (E-PDS) is a new activation method that has attracted extensive attention from researchers due to its good performance, simple and efficient reaction system, easy regulation, and good environmental characteristics. Anodic activation of PDS requires a sacrificial metal anode (such as Fe) to release metal ions (such as Fe 2+ ), which will quickly consume the life of the electrode. The cathode activation of PDS has a longer electrode life than the anode activation of PDS because the electrons gained at the cathode will have a certain protective effect on the material. However, the metal ion leaching rate of the cathode material of the current activated PDS is high, which also leads to a short service life of the electrode; and the degradation performance of the electrode material needs to be further improved. It can be seen that the development of an electrode material with low metal ion leaching, high degradation performance and long electrode life is one of the problems that need to be solved urgently. Summary of the invention

[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions: One of the objects of the present invention is to provide an iron catalytic material, comprising: an iron substrate and an oxygen-containing iron layer formed in situ on the surface of the iron substrate, wherein the oxygen-containing iron layer comprises one or more of γ-FeOOH, α-Fe2O3 or Fe3O4.

[0006] In some embodiments, the oxygen-containing iron layer includes γ-FeOOH, and the γ-FeOOH is a hydrotalcite-like lamellar structure. The γ-FeOOH has a lamellar diameter of 0.5-0.8 μm and a lamellar thickness of 0.04-0.05 μm.

[0007] In some embodiments, the oxygen-containing iron layer includes α-Fe2O3, and the α-Fe2O3 is a sea urchin-like structure. The sea urchin-like structure is composed of branch structures extending radially outward, and the length of the branch structure is 0.6-0.8 μm.

[0008] In some embodiments, the oxygen-containing iron layer includes Fe3O4, and the Fe3O4 is spherical particles with a diameter of 0.1-0.2 μm.

[0009] In some embodiments, the thickness of the oxygen-containing iron layer is 1-1.5 μm.

[0010] In some embodiments, the iron substrate is an iron sheet, an iron mesh, or foamed iron.

[0011] The second object of the present invention is to provide a method for preparing an iron catalytic material, comprising: in-situ etching an iron substrate with an iron salt solution with a concentration of 20-80 mM to form an oxygen-containing iron layer containing γ-FeOOH on the surface of the iron substrate to obtain a γ-FeOOH / Fe iron catalytic material.

[0012] By etching with an iron salt solution, an oxygen-containing iron layer composed of γ-FeOOH crystals can be grown in situ on the surface of the iron substrate. If the concentration of the iron salt solution is high, the substrate will collapse. If the concentration of the iron salt solution is low, the etching is incomplete and a uniform oxygen-containing iron layer cannot be formed.

[0013] In some embodiments, the iron salt contained in the iron salt solution includes one or a combination of ferric chloride, ferric sulfate, and ferric nitrate.

[0014] In some embodiments, the in-situ etching time is 20 to 60 minutes. If the etching time is too long, the iron substrate structure will be excessively lost, thereby causing the substrate to collapse, reducing its activation performance, and affecting the service life of the electrode; within this etching time range, a uniform and dense γ-FeOOH crystal layer can be grown on the surface of the iron substrate, and the iron substrate is well maintained.

[0015] The third object of the present invention is to provide a γ-FeOOH / Fe iron catalytic material, which is prepared by the method described in the above technical solution.

[0016] A fourth object of the present invention is to provide a method for preparing an iron catalytic material, comprising: The γ-FeOOH / Fe iron catalytic material is prepared by the method described above; In an inert atmosphere, the γ-FeOOH / Fe iron catalytic material is calcined at 300-500° C. to convert the γ-FeOOH therein into α-Fe2O3, so as to form an oxygen-containing iron layer containing α-Fe2O3 on the iron substrate, thereby obtaining an α-Fe2O3 / Fe iron catalytic material.

[0017] In some embodiments, the calcination is carried out at a heating rate of 2 to 10 °C / min to a temperature of 300 to 500 °C.

[0018] In some embodiments, the calcination time is 60 to 180 min. If the calcination time is too long, the iron substrate will be destroyed, thereby reducing the specific surface area, collapsing the pore size, and reducing its activation performance. Within this calcination time range, the γ-FeOOH crystal layer is fully converted into α-Fe2O3, and the iron substrate is well maintained.

[0019] A fifth object of the present invention is to provide an α-Fe2O3 / Fe iron catalytic material, which is prepared by any of the methods described above.

[0020] A sixth object of the present invention is to provide the use of the iron catalytic material in electrochemically activating persulfate to degrade organic pollutants.

[0021] In some embodiments, the organic pollutants include one or a combination of pesticide pollutants (such as atrazine), antibiotics, and organic dyes.

[0022] The γ-FeOOH / Fe catalytic material and the α-Fe2O3 / Fe iron catalytic material provided by the present invention can both effectively reduce the leaching of iron ions.

[0023] A seventh object of the present invention is to provide a method for degrading pollutants, comprising: The iron catalytic material is used as a cathode and placed together with an anode in a reaction solution, wherein the reaction solution includes a supporting electrolyte, a persulfate and a pollutant; Apply 2~3 mA / cm 2 The current density is set to perform an electrochemical degradation reaction so that the iron catalytic material catalyzes the activation of persulfate, thereby degrading the pollutants.

[0024] When pure iron is used as cathode, pure iron electrode continues to precipitate and consume iron ions, so that electrode life is short. And using the iron catalytic material of the present invention as cathode, the oxygen-containing iron layer on the surface of the catalytic material can achieve the capture of precipitated iron ions, so that Fe ions are fixed on the oxygen-containing iron layer, reducing ion leaching, and reaching the purpose of extending electrode life. At the same time, leaching iron ions in the solution too much also can cause the quenching of active species in the solution, loss PDS, reduce degradation effect, therefore modify the surface oxygen-containing iron layer, reduce ion leaching, and can also maintain efficient long-term pollutant degradation process. Relative to pure iron, the cathode of the present invention shows similar pseudo-first-order pseudo-first-order kinetic coefficients in the effect of degrading pollutants.

[0025] In some embodiments, the anode is a DSA electrode.

[0026] In some embodiments, the concentration of persulfate in the reaction solution is 2-3 mM.

[0027] In some embodiments, the concentration of pollutants in the reaction solution is above 10 ppm, that is, the electrochemical degradation reaction system can effectively degrade pollutants with a concentration of above 10 ppm in the reaction solution, and has a high sensitivity.

[0028] In some embodiments, the cathode uses a γ-FeOOH / Fe iron catalytic material or an α-Fe2O3 / Fe iron catalytic material. During the electrochemical degradation reaction, the γ-FeOOH and α-Fe2O3 in the γ-FeOOH / Fe iron catalytic material or the α-Fe2O3 / Fe iron catalytic material can be converted into Fe3O4 during the activation of persulfate, thereby forming a Fe3O4 / Fe iron catalytic material, and the Fe3O4 / Fe iron catalytic material can continue to catalyze the activation of persulfate to degrade the pollutants. After 1 to 2 hours of electrochemical degradation using γ-FeOOH / Fe and α-Fe2O3 / Fe electrodes, the surface crystals are completely converted into Fe3O4, and the coexistence of γ-FeOOH and Fe3O4 or α-Fe2O3 and Fe3O4 may exist during the process.

[0029] During the electrochemical degradation process, Fe(III) in γ-FeOOH / Fe and α-Fe2O3 / Fe is converted into Fe(II) that can activate PDS. Fe(II) and Fe(III) form Fe3O4. After Fe3O4 is completely formed, the obtained Fe3O4 / Fe can continue to be used for electrochemical activation of PDS to degrade pollutants. It should be noted that γ-FeOOH / Fe and α-Fe2O3 / Fe can exist stably in an open environment. When they are not used, they will not trigger the above-mentioned conversion process. The above-mentioned conversion will only occur in the redox cycle of electrochemical degradation. The dynamic process of γ-FeOOH and α-Fe2O3 being converted into Fe3O4 during the electrochemical process can promote the continuous and stable degradation of pollutants.

[0030] γ-FeOOH / Fe and α-Fe2O3 / Fe can be simply prepared by in-situ etching and calcination, and are easy to store, but Fe3O4 cannot be directly formed in-situ on the surface of the iron substrate by a simple method, and Fe3O4 is not easy to store when not in use compared to γ-FeOOH and α-Fe2O3. Therefore, it is a better solution to first prepare γ-FeOOH / Fe or α-Fe2O3 / Fe by the method of the present invention, and use it as a cathode to promote its in-situ conversion into Fe3O4 / Fe during the electrochemical degradation process.

[0031] Compared with α-Fe2O3, the adsorption energy (-4.46 eV) of the O3 site in γ-FeOOH is higher than that of any site in α-Fe2O3. γ-FeOOH has a higher affinity for iron ions and is more easily converted into Fe3O4. The service life of the γ-FeOOH / Fe electrode is longer than that of α-Fe2O3 / Fe. Compared with γ-FeOOH / Fe, the α-Fe2O3 / Fe formed by calcination is more stable in an open environment, and its surface structure is not easily destroyed in a high humidity and oxygen environment. The process of α-Fe2O3 / Fe converting to Fe3O4 during the reaction is slightly slower, and the conversion is more gentle and complete. The partially reduced Fe 2+ Used to activate PDS, partially reduce Fe 2+ With Fe on the electrode 3+ Gradually form Fe3O4.

[0032] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present invention forms an oxygen-containing iron layer with a specific crystal structure on an iron substrate by etching or etching combined with calcination. The oxygen-containing iron layer can fix and protect metal active sites, reduce iron ion leaching during electrochemical activation of PDS, provide stability for the cathode material, and thus extend the service life of the cathode material; (2) The iron catalytic material provided by the present invention is used as the cathode, and the synergistic effect of electrochemical activation and transition metal material activation of PDS can effectively degrade pollutants under conditions of lower current density and lower PDS concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a schematic diagram of the process of preparing an iron catalytic material according to Example 2 of the present invention; Figure 2 is a SEM image of the γ-FeOOH / Fe material prepared in Example 1 of the present invention; Figure 3 is the XRD pattern of the γ-FeOOH / Fe material prepared in Example 1 of the present invention; Figure 4 is a HRTEM image of the γ-FeOOH / Fe material prepared in Example 1 of the present invention; Figure 5 is a SEM image of the α-Fe2O3 / Fe material prepared in Example 2 of the present invention; Figure 6 is the XRD pattern of the α-Fe2O3 / Fe material prepared in Example 2 of the present invention; Figure 7 is a HRTEM image of the α-Fe2O3 / Fe material prepared in Example 2 of the present invention; Figure 8 This is a SEM image of the cathode material in Example 1 after continuous electrochemical degradation for 2 h; Fig. 9 Is the XRD pattern of the cathode material in Example 1 after continuous electrochemical degradation for 2 h; Fig.10 This is a HRTEM image of the cathode material in Example 1 after continuous electrochemical degradation for 2 h; Fig.11 This is a diagram showing the effect of using γ-FeOOH / Fe electrochemically activated PDS to degrade atrazine; Fig.12 This is a diagram showing the effect of using α-Fe2O3 / Fe electrochemically activated PDS to degrade atrazine; Fig.13It is a comparison chart of the life span of the catalytic cathode materials of Example 1, Example 2 and Comparative Example 1 when performing long-term electrochemical activation of PDS to degrade atrazine (pesticide); Fig.14 is a photograph of the cathode material of Example 1 after the electrochemical degradation reaction lasted for 53 hours; Fig.15 is a photograph of the cathode material of Example 2 after 47 hours of continuous electrochemical degradation reaction; Fig.16 This is a photograph of the cathode material of Comparative Example 1 after continuous electrochemical degradation reaction for 18 hours; Fig.17 It is a comparison chart of the metal ion leaching amount of the catalytic cathode materials of Example 1, Example 2 and Comparative Example 1 during the long-term electrochemical activation PDS degradation of atrazine (pesticide). DETAILED DESCRIPTION

[0035] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0036] Unless otherwise specified, the raw materials and reagents used in the specific embodiments of the present invention are all commercially available.

[0037] Example 1 This embodiment provides a γ-FeOOH / Fe iron catalytic electrode material and a preparation method thereof, which specifically includes the following steps: A piece of foam iron material was cleaned. The specific cleaning process was as follows: the foam iron was soaked in 1 M HCl for 10 min, and then cleaned in deionized water and anhydrous ethanol for 10 min each; The cleaned foamed iron was immersed in a 60 mM FeCl3 solution for 30 min for in-situ etching. After etching, it was taken out and dried. A layer of γ-FeOOH was formed on the foamed iron by in-situ etching, thereby obtaining a γ-FeOOH / Fe material.

[0038] Figure 2 This is the SEM image of the γ-FeOOH / Fe material. It can be seen that the γ-FeOOH / Fe is a hydrotalcite-like lamellar structure with a flake diameter of about 0.6 μm and a flake thickness of about 0.044 μm. Figure 3is the XRD pattern of γ-FeOOH / Fe material. It can be seen that the XRD spectrum of γ-FeOOH / Fe has main diffraction peaks at 2θ of 27.07°, 36.39° and 46.87°. Figure 4 is the HRTEM image of γ-FeOOH / Fe material, showing the lattice spacing of 0.33 nm and 0.25 nm, which is consistent with the interplanar spacing of (120) and (031) planes in γ-FeOOH.

[0039] The γ-FeOOH / Fe material prepared in Example 1 was used to electrochemically activate persulfate (PDS) to degrade the pollutant atrazine. The specific operation was as follows: 250 mL of a solution containing 10 mg / L of the target pollutant atrazine and 50 mM Na2SO4 supporting electrolyte was added to an open 300 mL cylindrical glass container, and 3 mM PDS was added to the solution; a titanium-based dimensionally stable DSA was used as the anode (area 2×3 cm 2 ), using the γ-FeOOH / Fe prepared above (area 2×3 cm 2 ) material as the cathode, the anode and cathode were placed in the above solution, and 3 mA / cm 2 The electrochemical degradation reaction was carried out at a current density of 1.50 and the reaction time was 40 min. The above steps were repeated three times with the same γ-FeOOH / Fe cathode to test the effect of activated PDS on pollutant degradation in three cycles.

[0040] Fig.11 This is a diagram showing the effect of using γ-FeOOH / Fe electrochemically activated PDS to degrade atrazine. During the three cycles, γ-FeOOH / Fe was able to effectively activate PDS to degrade the pollutant atrazine during the cathode electrochemical activation process, and the activity did not weaken.

[0041] Example 2 This embodiment provides an α-Fe2O3 / Fe iron catalytic electrode material and a preparation method thereof, wherein the preparation process is as follows: Figure 1 As shown, the specific steps include: A piece of foam iron material was cleaned. The specific cleaning process was as follows: the foam iron was soaked in 1 M HCl for 10 min, and then cleaned in deionized water and anhydrous ethanol for 10 min each; The cleaned foamed iron was immersed in a 60 mM FeCl3 solution for 30 min for in-situ etching. After etching, it was taken out and dried. A layer of γ-FeOOH was formed on the foamed iron by in-situ etching, thereby obtaining a γ-FeOOH / Fe material. The γ-FeOOH / Fe material was naturally dried in a dry environment, then heated to 400 ℃ at a heating rate of 5 ℃ / min in a nitrogen atmosphere, and calcined at 400 ℃ for 120 min to obtain the α-Fe2O3 / Fe material.

[0042] Figure 5 This is the SEM image of the α-Fe2O3 / Fe material. It can be seen that the α-Fe2O3 / Fe presents a sea urchin-like structure, which is composed of branched structures extending radially outward. The length of the branched structure is about 0.67 μm. Figure 6 It is the XRD pattern of α-Fe2O3 / Fe material. It can be seen that the XRD spectrum of α-Fe2O3 / Fe material has main diffraction peaks at 2θ of 24.30°, 33.39°, 35.83°, 49.78° and 54.46°. Figure 7 is the HRTEM image of α-Fe2O3 / Fe material, showing lattice spacings of 0.25 nm and 0.37 nm, which is consistent with the interplanar spacings of (110) and (012) planes in γ-Fe2O3.

[0043] The same method as in Example 1 was adopted, and the α-Fe2O3 / Fe material prepared in Example 2 was used as the cathode to perform electrochemical activation of PDS to degrade pollutants. Fig.12 This is a diagram showing the effect of using α-Fe2O3 / Fe to activate PDS to electrochemically degrade atrazine. During the three cycles, α-Fe2O3 / Fe was able to effectively activate PDS to degrade the pollutant atrazine during the cathode electrochemical activation process, and the activity did not weaken.

[0044] In addition, after the electrochemical degradation reaction continued for 2 h, the cathode material in Example 1 was characterized by electron microscopy and XRD. Figure 8 This is a SEM image of the cathode material in Example 1 after the reaction lasted for 2 hours. It was found that during the electrochemical degradation reaction of the cathode in Example 1, the γ-FeOOH therein was transformed into spherical particles with a diameter of about 0.12 μm. Fig. 9 This is the XRD pattern of the cathode material in Example 1 after the reaction lasted for 2 h, which shows that γ-FeOOH is transformed into Fe3O4 during the electrochemical degradation process. Fig.10 This is the HRTEM image of the cathode material in Example 1 after continuous reaction for 2 h, which also proves that the original γ-FeOOH / Fe is transformed into Fe3O4 / Fe with lattice spacings of 0.25 nm, 0.30 nm and 0.15 nm.

[0045] After the electrochemical degradation reaction continued for 2 h, the cathode material in Example 2 was characterized by electron microscopy and XRD. The characterization results were similar to those mentioned above. SEM, XRD and HRTEM characterizations all showed that α-Fe2O3 / Fe was gradually converted into Fe3O4 / Fe during the electrochemical degradation reaction.

[0046] Example 3 This embodiment provides an iron catalytic electrode material and a preparation method thereof, which specifically includes the following steps: A piece of foam iron material was cleaned. The specific cleaning process was as follows: the foam iron was soaked in 0.5 M H2SO4 for 10 min, and then cleaned in deionized water and anhydrous ethanol for 10 min each; The cleaned foamed iron was immersed in a 20 mM Fe2(SO4)3 solution for 60 min for in-situ etching. After etching, it was taken out and dried. A layer of γ-FeOOH was formed on the foamed iron by in-situ etching to obtain γ-FeOOH / Fe material.

[0047] The γ-FeOOH / Fe material was naturally dried in a dry environment, then heated to 300 °C at a heating rate of 2 °C / min in a nitrogen atmosphere, and calcined at 300 °C for 180 min to obtain the α-Fe2O3 / Fe material.

[0048] 250 mL of a solution containing 10 mg / L of the target pollutant atrazine and 50 mM Na2SO4 as supporting electrolyte was added to an open 300 mL cylindrical glass container, and 2 mM PDS was added to the solution; a titanium-based dimensionally stable DSA was used as the anode (area 2×3 cm 2 ), respectively, using the γ-FeOOH / Fe and α-Fe2O3 / Fe materials (area 2×3 cm 2 ) as the cathode, the anode and cathode were placed in the above solution and 2 mA / cm 2 The electrochemical degradation reaction was carried out at a current density of 1.50 Å and the reaction time was 40 min. The above steps were repeated three times with the same γ-FeOOH / Fe cathode to test the effect of activated PDS on pollutant degradation in three cycles. The obtained effect was equivalent to that of Examples 1 and 2.

[0049] The above examples show that the electrochemical system with γ-FeOOH / Fe and α-Fe2O3 / Fe as cathode can be used at a lower current density (2~3 mA / cm 2 ) and lower PDS concentration (2~3 mM) conditions, PDS was effectively activated to degrade the pollutant atrazine, and the activity of the cathode material did not significantly weaken during long-term circulation.

[0050] Example 4 This embodiment provides an iron catalytic electrode material and a preparation method thereof, which specifically comprises the following steps: A piece of foam iron material was cleaned. The specific cleaning process was as follows: the foam iron was soaked in 1 M HNO3 for 10 min, and then cleaned in deionized water and anhydrous ethanol for 10 min each; The cleaned foamed iron was immersed in 80 mM Fe(NO3)3 solution for 20 min for in-situ etching. After etching, it was taken out and dried. A layer of γ-FeOOH was formed on the foamed iron by in-situ etching to obtain γ-FeOOH / Fe material.

[0051] The γ-FeOOH / Fe material was naturally dried in a dry environment, then heated to 500 ℃ at a heating rate of 10 ℃ / min in a nitrogen atmosphere, and calcined at 500 ℃ for 60 min to obtain the α-Fe2O3 / Fe material.

[0052] The γ-FeOOH / Fe material and α-Fe2O3 / Fe material prepared in this example were used as cathodes, respectively, and the electrochemical degradation reaction was carried out in the same manner as in Example 1. The obtained effects were equivalent to those in Examples 1 and 2.

[0053] Example 5 This embodiment provides an iron catalytic electrode material and a preparation method thereof, which specifically comprises the following steps: A piece of iron sheet was cleaned. The specific cleaning process was as follows: soak the iron sheet in 1 M HCl for 10 min, then clean it in deionized water and anhydrous ethanol for 10 min each; The cleaned iron sheet was immersed in a 60 mM FeCl3 solution for 30 min for in-situ etching. After etching, it was taken out and dried. A layer of γ-FeOOH was formed on the iron sheet by in-situ etching, thereby obtaining γ-FeOOH / Fe material.

[0054] The γ-FeOOH / Fe material was naturally dried in a dry environment, then heated to 400 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined at 400 °C for 120 min to obtain the α-Fe2O3 / Fe material.

[0055] The γ-FeOOH / Fe material and α-Fe2O3 / Fe material prepared in this example were used as cathodes, respectively, and the electrochemical degradation reaction was carried out in the same manner as in Example 1. The obtained effects were equivalent to those in Examples 1 and 2.

[0056] Example 6 This embodiment provides an iron catalytic electrode material and a preparation method thereof, comprising the following steps: A piece of iron mesh was cleaned. The specific cleaning process was as follows: the iron mesh was soaked in 1 M HNO3 for 10 min, and then cleaned with deionized water and anhydrous ethanol for 10 min each; The cleaned iron mesh was immersed in a 60 mM Fe(NO4)3 solution for 30 min for in-situ etching. After etching, it was taken out and dried. A layer of γ-FeOOH was formed on the iron mesh by in-situ etching to obtain γ-FeOOH / Fe material.

[0057] The γ-FeOOH / Fe material was naturally dried in a dry environment, then heated to 400 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined at 400 °C for 120 min to obtain the α-Fe2O3 / Fe material.

[0058] The γ-FeOOH / Fe material and α-Fe2O3 / Fe material prepared in this example were used as cathodes, respectively, and the electrochemical degradation reaction was carried out in the same manner as in Example 1. The obtained effects were equivalent to those in Examples 1 and 2.

[0059] Comparative Example 1 Comparative Example 1: Pure foamed iron was used as the cathode to electrochemically activate PDS to degrade atrazine.

[0060] Fig.13 The figure is a life comparison chart of the cathodes of Example 1, Example 2 and Comparative Example 1 during long-term electrochemical activation of PDS to degrade atrazine (pesticide), indicating that the amount of metal ions precipitated by pure foamed iron as a cathode is much greater than the amount of metal ions precipitated by the electrode with an oxygen-containing iron layer on the surface. The service life of γ-FeOOH / Fe and α-Fe2O3 / Fe are 53 h and 47 h, respectively, which are 2.94 times and 2.61 times that of the original Fe (18 h), respectively. It shows that the oxygen-containing iron layer formed on the electrode surface obtained by etching and calcining prevents the leaching of internal metal ions under the synergistic effect of the electric field, thereby extending the service life of the electrode. During use, PDS can be effectively activated to degrade the pollutant atrazine during the cathode electrochemical activation process.

[0061] Fig.14 , Fig.15 , Fig.16The photos of the cathode materials in Example 1, Example 2 and Comparative Example 1 after 53 h, 47 h and 18 h of continuous electrochemical degradation reaction respectively show that the cathode of Comparative Example 1 is broken due to severe precipitation of Fe ions. Although the cathodes of Example 1 and Example 2 have a certain degree of surface damage due to the precipitation of metal ions, the amount of metal ion precipitation is much less than that of Comparative Example 1. This shows that under the synergistic effect of the electric field, the oxygen-containing iron layer on the surface of the cathode materials in Example 1 and Comparative Example 2 can effectively prevent the leaching of internal iron ions, thereby extending the service life of the electrode. The service life of γ-FeOOH / Fe and α-Fe2O3 / Fe in Example 1 and Example 2 are 53 h and 47 h, respectively, which are 2.94 times and 2.61 times that of Fe in Comparative Example 1 (about 18 h service life).

[0062] Fig.17 It is a comparison chart of the metal ion leaching amount during the long-term degradation process of the cathode materials in Example 1, Example 2 and Comparative Example 1. The amount of iron ion leaching of the cathode material in Comparative Example 1 is the largest when sampling and testing is performed at each time node, which is much larger than the ion leaching amount of the materials in Example 1 and Example 2. At the same time, the ion leaching amount in Example 1 is slightly lower than the ion leaching amount of the material in Example 2.

[0063] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that the time for in-situ etching of the foamed iron with FeCl3 solution is 90 min. It is found that the etching time is too long, resulting in more loss of the iron substrate, decreased activation performance, and weakened degradation effect.

[0064] Comparative Example 3 Comparative Example 3 is basically the same as Example 3, except that the calcination time is 240 min. It is found that the longer calcination time leads to the destruction of the iron substrate, the reduction of the specific surface area, the collapse of the pore size, the decrease of the activation performance, and the weakening of the degradation effect.

[0065] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0066] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0067] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. An iron catalytic material, characterized in that include: An iron substrate and an oxygen-containing iron layer in-situ formed on the surface of the iron substrate, wherein the oxygen-containing iron layer comprises one or more of γ-FeOOH, α-Fe2O3 or Fe3O4.

2. The iron catalytic material according to claim 1, characterized in that: The oxygen-containing iron layer includes γ-FeOOH, the γ-FeOOH is a hydrotalcite-like lamellar structure, the γ-FeOOH has a lamellar diameter of 0.5-0.8 μm, and a lamellar thickness of 0.04-0.05 μm; And / or, the oxygen-containing iron layer includes α-Fe2O3, the α-Fe2O3 is a sea urchin-like structure, the sea urchin-like structure is composed of branch structures extending radially outward, and the length of the branch structure is 0.6-0.8 μm; And / or, the oxygen-containing iron layer comprises Fe3O4, and the Fe3O4 is spherical particles with a diameter of 0.1-0.2 μm; And / or, the thickness of the oxygen-containing iron layer is 1-1.5 μm; And / or, the iron substrate is an iron sheet, an iron mesh or foamed iron.

3. A method for preparing an iron catalytic material, characterized in that: include: The iron substrate is in-situ etched with an iron salt solution having a concentration of 20 to 80 mM to form an oxygen-containing iron layer containing γ-FeOOH on the surface of the iron substrate to obtain a γ-FeOOH / Fe iron catalytic material; Preferably, the iron salt contained in the iron salt solution includes one or a combination of ferric chloride, ferric sulfate, and ferric nitrate; Preferably, the in-situ etching time is 20 to 60 min.

4. An iron catalytic material, characterized in that It is prepared by the method described in claim 3.

5. A method for preparing an iron catalytic material, characterized in that: include: The γ-FeOOH / Fe iron catalytic material is prepared by the method according to claim 3; In an inert atmosphere, the γ-FeOOH / Fe iron catalytic material is calcined at 300-500° C. to convert the γ-FeOOH therein into α-Fe2O3, so as to form an oxygen-containing iron layer containing α-Fe2O3 on the iron substrate, thereby obtaining an α-Fe2O3 / Fe iron catalytic material.

6. The preparation method according to claim 5, characterized in that: The calcination is carried out by heating the temperature to 300-500°C at a heating rate of 2-10°C / min; And / or, the calcination time is 60 to 180 min.

7. An iron catalytic material, characterized in that: It is prepared by the method described in claim 5 or 6.

8. Use of the iron catalytic material according to claim 1, 2, 4 or 7 in electrochemically activating persulfate to degrade organic pollutants; Preferably, the organic pollutants include one or a combination of pesticide pollutants, antibiotics, and organic dyes; more preferably, the organic pollutants include atrazine.

9. A method for degrading pollutants using electrochemically active persulfate, characterized in that: include: The iron catalytic material according to claim 1, 2, 4 or 7 is used as a cathode and placed together with an anode in a reaction solution, wherein the reaction solution comprises a supporting electrolyte, a persulfate and a pollutant; Apply 2~3 mA / cm 2 The current density is set to perform an electrochemical degradation reaction so that the iron catalytic material catalyzes the activation of persulfate, thereby degrading the pollutants.

10. The method according to claim 9, characterized in that: The anode is a DSA electrode; and / or, the concentration of persulfate in the reaction solution is 2-3 mM; And / or, the cathode adopts the γ-FeOOH / Fe iron catalytic material of claim 4 or the α-Fe2O3 / Fe iron catalytic material of claim 7. During the electrochemical degradation reaction, the γ-FeOOH and α-Fe2O3 in the γ-FeOOH / Fe iron catalytic material or the α-Fe2O3 / Fe iron catalytic material can be converted into Fe3O4 during the activation of persulfate, thereby forming a Fe3O4 / Fe iron catalytic material, and the Fe3O4 / Fe iron catalytic material can continue to catalyze the activation of persulfate to degrade the pollutants.

Citation Information

Cited By

  • Iron-based cathode material for wastewater treatment as well as preparation method and application of iron-based cathode material

    CN120757204A